Pre‐eruptive inflation caused by gas accumulation: Insight from detailed gas flux variation at Sakurajima volcano, Japan. Issue 21 (15th November 2016) - Kazahaya, Ryunosuke; Shinohara, Hiroshi; Mori, Toshiya; Iguchi, Masato; Yokoo, Akihiko
Abstract: Sulfur dioxide (SO2 ) emission rate observations were made at Sakurajima volcano, Japan, to quantify the relationship between the SO2 emission rate and inflation prior to Vulcanian explosions. The explosions associated with precursory inflation events were preceded by decreases in SO2 emission rates by 10–60 min. The amounts of accumulated gas were calculated using time series of SO2 emission rate. The amounts of accumulated SO2 and increases in strain records before the explosions showed a positive correlation. The volume increase of a deformation source calculated using the strain records was of the comparable order of magnitude as the volume of the accumulated volcanic gas. The results suggest that the inflations before the explosions were caused by the gas accumulation. Key Points: The decrease in volcanic gas flux before Vulcanian eruption at Sakurajima, Japan, was quantified A correlation was found between the gas flux and geodetic records Inflation prior to Vulcanian eruption is likely caused by gas accumulation in the conduit